Evaluating Stocker Steer Gains on Tallgrass Native Range with Two Burn Dates and Spices in Mineral - J. K. Farney (Kansas Agricultural Experiment Station Research Reports, 2020)
Objective:The overall objective of this study was to evaluate management practices that may impact stocker steer gains on a 90-day double stocking grazing system in tallgrass native range. Specific objectives include evaluating the timing of burning, addition of spices in a complete free-choice mineral, and determination if the effects are additive. Study Description:Two pasture burning times (March or April) and free-choice mineral with or without addition of spices were evaluated using 281 head of stocker steers on eight pastures of tallgrass native range. The spices included garlic oil in powder form and Solace (Wildcat Feeds LLC). Cattle were weighed at the start of the study and the end. Steers grazed pastures for 87 days. Data analyzed included average daily gain, total gain, and final weight. The Bottom Line:Burning pastures in April results in a greater calf gain than burning in March, while the addition of spices to a free-choice complete mineral shows promise as a cost-effective method to increase gains in stocker steers on tallgrass native range.
Keywords: essential oils; average daily gain; smoke management